Cooperative Learning dalam Pembelajaran Bahasa Arab Berbasis Kurikulum 2013 - Jepri Nugrawiyati (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2017)
Abstract: In the era of globalization, teachers are required to continue to make innovations in learning. Coupled with the presence of the curriculum in 2013 yangdikembangkan to improve and balance the soft skills and hard skills that form of attitudes, skills and knowledge. Cooperative learning is becoming one of the choices in learning to prioritize cooperation in solving the problems to apply knowledge and skills in order to achieve the learning objectives. Arabic becomes an important part in the arrangement of the curriculum in 2013, and with cooperative learning is learning the language is not only studying the language associated with the grammar, protocols for reading and writing, but should reflect the competence of the attitude of speaking polite, how to think scientifically, and language skills communicative.Keywords: Cooperative Learning, The Curriculum In 2013, Learning Arabic